Peran Kepala Sekolah dalam Meningkatkan Manajemen Tenaga Kependidikan - Syaikhudin, M (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
The principal as an educational leader has a very influential leadership role in improving the management of the teaching staff in schools. The success and failure of an institution is largely determined by the role of the principal in managing the education personnel available at the school, the principal is the determinant of the direction in realizing the vision and mission of the school's goals., it shows that the role of leadership is carried out by the principal in improving the management of the education staff, namely by providing direction and guidance in every problem faced by education personnel in every learning process, the performance of educational staff at it is good enough, everything is supported by adequate infrastructure or facilities, and this research aims to find out how the role of the principal's leadership in improving the management of education personnel by developing potential. This study used a qualitative research conducted at with a descriptive research design. The techniques used in this study researchers used data collection techniques carried out by observation, interviews, and documentation.